2019
DOI: 10.1177/0706743719892709
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Clozapine Rechallenge in a Case of Clozapine-Induced Myocarditis

Abstract: Objective: Protocol for clozapine rechallenge in patients with a history of clozapine-induced myocarditis. Method: Clozapine-related cardiovascular adverse effects including myocarditis and cardiomyopathy have limited its widespread use in treatment-resistant schizophrenia. Here, we present a case of clozapine-induced myocarditis and successful cautious rechallenge. Ms. AA, a young female patient with severe psychosis developed myocarditis during her initial clozapine titration phase, which was thus discontinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Exploring previous case reports describing instances of clozapine rechallenge, Manu and colleagues found that while rechallenge was a rational option for patients with neutropenia or neuroleptic malignant syndrome, it carried major risks for patients with agranulocytosis or myocarditis 27 . Still, there are a few reports of clozapine‐induced myocarditis in which clozapine was successfully resumed (after temporary discontinuation) by increasing the dosage more cautiously while measuring CRP and troponin levels in close coordination with cardiologists 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…Exploring previous case reports describing instances of clozapine rechallenge, Manu and colleagues found that while rechallenge was a rational option for patients with neutropenia or neuroleptic malignant syndrome, it carried major risks for patients with agranulocytosis or myocarditis 27 . Still, there are a few reports of clozapine‐induced myocarditis in which clozapine was successfully resumed (after temporary discontinuation) by increasing the dosage more cautiously while measuring CRP and troponin levels in close coordination with cardiologists 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, many of the case reports included in this review described marked improvements in patient symptoms and functioning prior to the development of myocarditis that could not be sustained following clozapine discontinuation. However, guidelines for performing a clozapine rechallenge in this clinical context have not been developed, although protocols have been proposed (Shivakumar et al, 2019). Our review sought to identify potential clinical factors associated with successful clozapine rechallenge to inform future guideline development.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with diuretics, angiotensin converting enzyme inhibitors, beta-blockers and steroids might be needed [ 13 ]. In general, future rechallenge of clozapine is not recommended due to the high risk of recurrence of cardiac problems [ 32 , 33 ]. However, due to the lack of an equally effective alternative antipsychotic, sometimes rechallenge is embarked, after carefully weighing the benefits and risks.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of an equally effective alternative antipsychotic, sometimes rechallenge is embarked, after carefully weighing the benefits and risks. Shivakumar et al (2019) proposed a protocol for clozapine rechallenge in which they suggest a strategy of slow titration combined with interruption of titration once any indices increase (monocytes, neutrophils, eosinophils, or CRP) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%